Production of branched-chain very-long-chain fatty acids by fatty acid elongases and their tissue distribution in mammals - Tanno, Honoka; Sassa, Takayuki; Sawai, Megumi; Kihara, Akio (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2021)
Although most mammalian fatty acids (FAs) are straight-chain, there also exist branched-chain FAs such as iso- and anteiso-FAs, especially in the meibomian glands. Meibum lipids, which are secreted from the meibomian glands and are important for dry eye prevention, contain abundant branched-chain lipids, such as cholesteryl esters and wax esters with chain-lengths of ≥C21 (very-long-chain; VLC). However, the exact tissue distribution of branched-chain lipids or the enzymes involved in the production of branched-chain VLCFAs has remained poorly understood. Here, we revealed that FA elongases ELOVL1, ELOVL3, and ELOVL7, of the seven mammalian ELOVL isozymes, elongated saturated branched-chain acyl-CoAs. ELOVL3 was highly active toward iso-C17:0 and anteiso-C17:0 acyl-CoAs and elongated them up to iso-C23:0 and anteiso-C25:0 acyl-CoAs, respectively. ELOVL1 elongated both iso- and anteiso-C23:0 acyl-CoAs to C25:0 acyl-CoAs. By establishing a liquid chromatography-tandem mass spectrometry method capable of separating branched- and straight-chain lipids, we showed that essentially all of the cholesteryl esters and 88% of the wax esters in the mouse meibomian glands are branched. In Elovl1 mutant mice, the levels of ≥C24:0 branched-chain cholesteryl esters and ≥C25:0 branched-chain wax esters were decreased, indicating that ELOVL1 indeed elongates branched-chain VLC acyl-CoAs in vivo. In addition, substantial amounts of ceramides containing branched-chain FAs were present in the skin, meibomian glands, and liver. Our findings provide new insights into the molecular mechanisms that create FA and lipid diversity. [Display omitted] •Saturated branched-chain fatty acids are elongated by ELOVL1, ELOVL3, and ELOVL7.•ELOVL1 produces very-long-chain branched-chain fatty acids in the meibomian glands.•Branched-chain fatty acids are incorporated into ceramides.•Branched-chain ceramides are present in the meibomian glands and liver.